Determinants of Islamic Financial Planning for Marriage in Generation Z - Ma’mun, Lalu M Masysyath Nawawi; Syamlan, Yaser Taufiq; Mohammad , Che Adenan (STAI Serdang Lubuk Pakam, 2024)
Islamic financial planning for marriage is important for Muslims, but is often hampered by high consumptiveness, low financial literacy, and high divorce rates due to financial problems. This study aims to analyze the determinants of Islamic financial planning for marriage in Generation Z. The following is a summary of the section. The variables of attitude, subjective norms, and perceived behavioral control will affect the dependent variable through the mediation of marriage intention, while financial self-efficacy has a direct effect on Islamic financial planning for marriage. This study was conducted in Jabodetabek with 175 respondents using purposive sampling and analyzed with SEM-PLS. The results showed that financial self-efficacy has a positive and significant effect on financial planning for marriage. Attitude, Subjective Norm, and Perceived Behavioural Control also have a positive and significant effect on marriage intention. Marriage intention as an intervening variable has a positive and significant impact on Islamic financial planning for marriage. The findings emphasise the importance of improving financial literacy and providing Islamic financial planning education programs for generation Z to prepare for marriage and reduce the risk of financial problems.